1-cosA +sinA/sinA+cosA-1=1+sinA/cosA
Attachments:
![](https://hi-static.z-dn.net/files/d4f/6234e56fbe92ef98536c6f23c33b8ed7.jpg)
Answers
Answered by
1
Hello
I will follow u
But you have to mark me as brain liest
Here is your answer
LHS = (sinA-cosA+1)/(sinA+cos-1) = (1 + sinA) (1 - sinA)/cos A(1 - sinA) = 1 - sin2A/cos A(1 - sinA) = cos2A/cos A(1 - sinA) = cosA/(1 - sinA) = 1/ (1/cosA - sinA/cosA) = 1/(secA - tanA) = RHS Hence Proved
Thanks
Plz mark me as brain liest this
mannatmarya:
first tell
Similar questions